The Influence of Prior Statin Use on the Prevalence and Exacerbation of Chronic Obstructive Pulmonary Disease in an Adult Population - Kim, Joo-Hee; Choi, Hyo Geun; Kwon, Mi Jung; Kim, Ji Hee; Park, Ji-Young; Hwang, Yong Il; Jang, Seung Hun; Jung, Ki-Suck (Frontiers in Medicine, 2022)
Background: Statins have anti-inflammatory and antioxidant properties, and previous studies have reported the positive effects of statins on chronic obstructive pulmonary disease (COPD) outcomes. However, the effects of statins on the development and acute exacerbations of COPD remain unclear. Therefore, this study aimed to assess the relation between statin use and COPD occurrence in all participants and the link between statin use and COPD acute exacerbations in participants with COPD. Methods: This case-control study comprised 26,875 COPD participants and 107,500 control participants who were 1:4 matched from the Korean National Health Insurance Service-Health Screening Cohort. Conditional logistic regression was used to evaluate the probability of COPD occurrence associated with previous statin use. In addition, unconditional logistic regression was employed to assess the risk of exacerbations related to statin use among COPD participants. These relations were estimated in subgroup analysis according to statin type (lipophilic vs. hydrophilic). Results: The association between previous statin use and the occurrence of COPD did not reach statistical significance in the overall population (adjusted odds ratio [aOR]=0.96, 95% confidence interval [CI]=0.93-1.00, P=0.059). However, statin use decreased the probability of exacerbations in participants with COPD (aOR=0.79, 95% CI=0.74-0.85, P<0.001). Lipophilic statins decreased the probability of exacerbations, whereas hydrophilic statins were not associated with a decreased likelihood of exacerbations (aOR=0.78, 95% CI=0.72-0.84, P<0.001 for lipophilic statins; aOR=0.89, 95% CI=0.78-1.02, P=0.102 for hydrophilic statins). Discussion: Statin use was not associated with the occurrence of COPD in the adult population. However, statin use was associated with a reduced probability of exacerbations in participants with COPD, with a greater risk reduction with lipophilic statin use.